Heat Treatment Conventional and Novel Applications - Czerwinski, Frank (IntechOpen, 2012)
Heat treatment and surface engineering are seen as crucial elements in the design and manufacture of strategic components in a wide range of market sectors and industries including air, sea and land transportation, energy production, mining, defense or agriculture. This book offers a broad review of recent global developments in an application of thermal and thermochemical processing to modify the microstructure and properties of a wide range of engineering materials. Although there is no formal partition of the book, chapters represent two different application areas of heat treatment. The first group covers the conventional heat treatment with processing of bearing rings, wrought and cast steels, aluminum alloys, fundamentals of thermochemical treatment, details of carbonitriding and a design of cooling units. The second group describes a use of non-conventional thermal routes during manufacturing cycles of such materials as vanadium carbides, titanium dioxide, metallic glasses, superconducting ceramics, nanoparticles, metal oxides, battery materials and slag mortars. A mixture of conventional and novel applications, exploring a variety of processes employing heating, quenching and thermal diffusion, makes the book very useful for a broad audience of scientists and engineers from academia and industry.